Neoantigen Vaccines Pass the Immunogenicity Test. Issue 10 (October 2017) - Linette, Gerald P.; Carreno, Beatriz M.
Abstract : Neoantigens arising from tumor-specific genomic alterations constitute authentic non-self antigens and represent a new class of targets for cancer immunotherapy. Recent reports on various vaccine platforms targeting neoantigens suggest a basis for precision therapies customized to each patient's tumor mutational profile.